04.10 Chronic inflammation regulates the mrna stabilome in rheumatoid arthritis fibroblast-like synoviocytes. (1st March 2017) - Loupasakis, Konstantinos; Kuo, David; Sohn, Christopher; Syracuse, Bethany; Giannopoulou, Eugenia G; Park, Sung Ho; Rätsch, Gunnar; Ivashkiv, Lionel B; Kalliolias, George D
Abstract : Background: Chronic synovial inflammation is a hallmark of rheumatoid arthritis (RA). During the long-term course of RA synovitis, chronic exposure of FLS to pro-inflammatory cytokines, such as TNF, induces a constellation of genes, which perpetuate synovial inflammation and provoke joint damage. Inflammation-induced gene expression evolves in a temporal order and involves two integrated processes: transcription and mRNA decay. Although the molecular mechanisms regulating transcription are well characterised, little is known about the impact of mRNA stability on gene expression and the genome-wide impact of chronic inflammation on decay rates of mRNA transcripts in RA FLS. Materials and methods: Chronic synovitis was modelled ex vivo by long-term exposure of RA FLS to TNF. RNA-sequencing was performed, gene-transcripts were quantified, and DESeq2 was used for differential testing between TNF treated and control libraries. For pathway analysis, MSigDB and Panther were used. Differentially stable gene transcripts were identified between time points of TNF stimulation by specific statistical analytical tools. Results: In our experimental system, long-term exposure of FLS to TNF induces a biphasic gene expression program. Initially, the inducible transcriptome consists primarily of unstable transcripts, but progressively switches and becomes dominated by very stable transcripts. This temporal switch is due to: a) TNF-induced prolonged stabilisation of previously unstable transcripts that enables progressive transcript accumulation over days and b) sustained expression and late induction of very stable transcripts. TNF-induced mRNA stabilisation in RA FLS occurs during the late phase of TNF response, is MAPK-dependent, and involves several genes with pathogenic potential, such as pro-inflammatory cytokines (eg, IL-6), a series of neutrophil-recruiting chemokines (eg, CXCL1, CXCL3, IL-8/CXCL8), CCL2, and PTGS2. Conclusions: These results provide the first insights into genome-wide regulation of mRNA stability by TNF in RA FLS, and highlight the potential contribution of dynamic regulation of the mRNA stabilome during the chronic course of RA synovitis. Inhibition of inflammation-induced mRNA-stabilising pathways may offer new opportunities for therapeutic intervention in RA synovitis. The results of the current study support a model where continuously active transcription in concert with mRNA stabilisation shape the aggressive behaviour of FLS during the chronic course of RA synovitis.